Novel water‐soluble polymer coatings control NPK release rate, improve soil quality and maize productivity. Issue 42 (8th June 2021) - Akhter, Mohsan; Shah, Ghulam Abbas; Niazi, Muhammad Bilal Khan; Mir, Saad; Jahan, Zaib; Rashid, Muhammad Imtiaz
Abstract: We investigated different combinations of polymers (5% each) (i) starch, gelatin (polymer coating; PC‐1), (ii) polyvinyl alcohol (PVA), gum Arabica (PC‐2), (iii) PVA, gelatin (PC‐3), (iv) starch, gum Arabica (PC‐4), (v) gelatin, gum Arabica (PC‐5), (vi) starch, PVA (PC‐6), for coating NPK (17, 17:17) in a fluidized bed granulator. Morphological characterization indicated a uniform coating of all formulations on NPK granules. A slow release of N (PC‐3), P (PC‐6), and K (PC‐3) was observed in water. In soil, high mineral N (63%), plant‐available P (72%), and K (24%) were observed in PC‐3, PC‐5, and PC‐6, respectively than uncoated fertilizer. Microbial biomass NPK was also higher in these treatment. This resulted in higher maize yield (66%), N (114%), P (164%), and K (137%) uptakes and apparent N (267%), P (196%), and K (358%) recoveries from applied fertilizer in these treatments. Among these, PC‐3 resulted in an increase of 115% shoot N, 169% P and 138% K uptakes and 268% apparent N, 206% P and 361% K recoveries than uncoated fertilizer. Hence, coating of NPK with this biodegradable polymer combination controlled N, P, and K release and synchronized these nutrients availabilities with maize nutrients demand therefore resulted in higher maize crop yield and nutrient utilization efficiencies. Abstract :